2001
DOI: 10.1016/s0022-5347(05)65874-0
|View full text |Cite
|
Sign up to set email alerts
|

Inguinal Hernia After Radical Retropubic Prostatectomy for Prostate Cancer: A Study of Incidence and Risk Factors in Comparison to No Operation and Lymphadenectomy

Abstract: The incidence of inguinal hernia is clearly increased in men who have undergone radical retropubic prostatectomy plus pelvic lymph node dissection compared with those who undergo no surgery for prostate cancer. Inguinal hernia appears to develop more often in men with prostate cancer who undergo radical retropubic prostatectomy and pelvic lymph node dissection than in those who undergo pelvic lymph node dissection only. While surgical factors trigger hernial development, previous hernial surgery and post-prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 9 publications
4
69
1
1
Order By: Relevance
“…25 In other studies, the incidence of inguinal hernia was higher for RRP with PLND than PLND alone. 9,21 On the other hand, Stranne et al 13 have shown that there was no significant difference between RRP with PLND and PLND alone, using a retrospective patient-administered questionnaire. As for laparoscopic prostatectomy (LRP) that is carried out with a minimum incision, the incidence of inguinal hernia has been reported to be as high as that with open RRP.…”
Section: -15mentioning
confidence: 99%
See 1 more Smart Citation
“…25 In other studies, the incidence of inguinal hernia was higher for RRP with PLND than PLND alone. 9,21 On the other hand, Stranne et al 13 have shown that there was no significant difference between RRP with PLND and PLND alone, using a retrospective patient-administered questionnaire. As for laparoscopic prostatectomy (LRP) that is carried out with a minimum incision, the incidence of inguinal hernia has been reported to be as high as that with open RRP.…”
Section: -15mentioning
confidence: 99%
“…Previous abdominal surgery, 6,16 sub-clinical inguinal hernia 7,17,18 and the length of incision 16,19 are supposed to be related to post-operative inguinal hernia. Age 5,6,9,[15][16][17][18]20 and anastomic stricture 9,14,17,18,20,21 have been suggested as risk factors in some studies, but not in others. Resection of endopelvic fascia 7 and retraction of the vasa deferentia by a retractor 8 are probably not the causative factors.…”
Section: -15mentioning
confidence: 99%
“…Since the first report by Regan et al in 1996 [1], the high incidence of postoperative inguinal hernia (IH) has been recognized as a common complication of RRP. The incidence of IH after RRP has been reported to range from 12 % to 38.7 % [1][2][3][4][5][6][7]. Furthermore, reportedly more than 90 % of IH after RRP was indirect hernia [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that 7 to 21% of men may require inguinal hernia repair around 2 years after prostate surgery (Lodding et al, 2001;Lughezzani et al;Sun et al, 2010). These rates were found to be higher in men after radical prostatectomy as compared to prostate biopsy, transurethral resection, or open prostatectomy for a benign disease (Sun et al, 2010).…”
Section: Surgerymentioning
confidence: 99%
“…These rates were found to be higher in men after radical prostatectomy as compared to prostate biopsy, transurethral resection, or open prostatectomy for a benign disease (Sun et al, 2010). Rates were also higher in men who underwent lymph node dissection or radiation therapy (Lodding et al, 2001;Lughezzani et al, 2010). Inguinal hernia is a post operative problem that was not emphasized in the literature.…”
Section: Surgerymentioning
confidence: 99%